FROM INFORMALITY TO FORMALISM: THE BRAND AS A MEANS OF DRIVING SMALL BUSINESS - Donato, Ana Carolyna Cazé; Simões, Rodrigo de Oliveira (Seven Editora, 2025)
Trademark registration has gained relevance, especially after the pandemic, being essential for small, medium, and large entrepreneurs to stand out in the market. Intellectual and Industrial Property are regulated by several laws, with a focus on the protection of innovations and trademarks.DOI: https://doi.org/10.56238/sevened2024.037-130